Automated phenotyping of plant shoots using imaging methods for analysis of plant stress responses - a review - Humplík, Jan F; Lazár, Dušan; Husičková, Alexandra; Spíchal, Lukáš (Plant methods, 2015)
Current methods of in-house plant phenotyping are providing a powerful new tool for plant biology studies. The self-constructed and commercial platforms established in the last few years, employ non-destructive methods and measurements on a large and high-throughput scale. The platforms offer to certain extent, automated measurements, using either simple single sensor analysis, or advanced integrative simultaneous analysis by multiple sensors. However, due to the complexity of the approaches used, it is not always clear what such forms of plant phenotyping can offer the potential end-user, i.e. plant biologist. This review focuses on imaging methods used in the phenotyping of plant shoots including a brief survey of the sensors used. To open up this topic to a broader audience, we provide here a simple introduction to the principles of automated non-destructive analysis, namely RGB, chlorophyll fluorescence, thermal and hyperspectral imaging. We further on present an overview on how and to which extent, the automated integrative in-house phenotyping platforms have been used recently to study the responses of plants to various changing environments.
Keywords: Biomass production; Shoot growth; Plant phenotyping; Thermal imaging; RGB digital imaging; Chlorophyll fluorescence imaging; Hyperspectral imaging